Comparing the Effect of Role-playing and Lecturing on Learning the Communication Skills Among Health Workers of Kerman Health Centers, Iran - Roghaye Ershad Sarabi; Maryam Salmani; Elham Danesh; Arash Farvahari (Kerman University of Medical Sciences, 2020)
Background: The proper health worker-patient communication is one of the main factors that affect patients' satisfaction and improve healthcare outcomes. Objectives: The current study aimed at comparing the effect of the two widely used teaching methods of role-playing and lecturing on learning the communication skills among health workers of Kerman health centers in Iran.Methods: The current intervention study included all health workers in Kerman City as the statistical population of whom 120 selected by the census method as the study samples were randomly assigned to three groups of 40 subjects. The first group was trained by role-playing and the second group by lecturing; the third group, as control, received no training. All the subjects completed the Barton standard relationship communication skills questionnaire before and after the intervention. Considering the non-normal distribution of data, the nonparametric Wilcoxon test was used. The data were then analyzed in SPSS software.Results: The mean age of the subjects was 38.54±8.29 years, and 46.7% of them had a high school diploma; 86.7% were married, and 74.2% were females. Based on the findings, the average score of communication skills in the role-playing group increased from 2.90 to 4.29 after the intervention, which was statistically significant (P <0.001).Conclusion: The average score of communication skills (i e, verbal, listening, and feedback skills) in the role-playing group was higher than those of the lecturing and control groups. Therefore, it can be concluded that the role-playing method can be useful in teaching communication skills.